APPLICATION OF SIMPLE SCIENCE EXPERIMENTAL METHODS THROUGH ECOPRINT ACTIVITIES TO IMPROVE THE COGNITIVE ABILITIES AND CREATIVITY OF EARLY CHILDREN AT NADA ASHOBAH IT KINDERGARTEN - Titien Ruswanti; Rachma Hasibuan (International Journal of Teaching and Learning, 2024)
An effective learning method to stimulate children's cognitive abilities and creativity is simple science experiments, such as ecoprint activities. Ecoprint is a printing technique using natural materials such as leaves and flowers, which can enhance children's cognitive abilities and creativity. The purpose of this study is to improve the cognitive abilities and creativity of Group B children through the enjoyable activity of ecoprint. This study uses a descriptive qualitative approach and was conducted at TK IT Nada Ashobah Wiyung Surabaya, with Group B children as the subjects. Data was obtained through observation and interviews with Group B teachers, then analyzed using the Miles and Huberman data analysis model, which consists of data collection, data reduction, data presentation, and conclusion drawing/verification. The results of the study show that ecoprint activities can improve children's cognitive abilities and creativity. Children learn to recognize the characteristics of various plants, observe, analyze, and combine leaf shapes to create interesting pictures. This activity also develops critical thinking and problem-solving skills, as well as increases children's curiosity and exploration.